A Study Of Light Through Colour And The Body Materials In Producing A Contemporary Installation - Maria, Binti Shaari (Universiti Malaysia Sarawak(UNIMAS), 2019)
The purpose of this research is to explore the light through the physicality of body materials producing colours in artwork visually. The research constructed on the suitable body materials in the study of light through colour is analysed in order to be identified and applied into final artwork as contemporary installation. Light and colour is not a solid material and cannot be hold except for sight. We can only state that light and colours do exist based on our sight sense. The methodology used in this research is in qualitative form. The data obtained from observation, experimentation, and data collection is then applied to the final artwork.